METHOD FOR OBTAINING SPECIAL, WINTER AND HIGH-FROST RESISTANT (ARCTIC) AIRCRAFT LUBE OILS - Budarov, I. P. (1962)
Translation of Byulleten' izobreteniy, no.l4, 1962, 66 (Soviet' patent, c1ass 23c, 1, no. 73785, 383102, August 18, 1948. pub1ished now for. tbe first time).